2022
DOI: 10.1590/fst.118621
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of parameters in restaurant food waste for use as poultry rations

Abstract: One way to use food industry wastes is to feed the livestock and poultry. Applying appropriate management methods for the optimal use of agricultural waste in the preparation of livestock and poultry feed increases productivity and reduces damage to agricultural and conversion industries and the use of new resources in animal and poultry feed. In this paper, in order to investigate the possibility of recycling food waste as poultry feed, the waste produced in a restaurant has been used. The parameters of fat p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
1
0
0
Order By: Relevance
“…Due to the nature of the food waste streams, previous studies might not attempt to make food waste-based diets isonitrogenous or isocaloric compared to the control diets 21 . Similar to this study, the protein and fat content in the food waste-based diet reported by Garnida et al 22 were also higher than the control diet.…”
Section: Introductionsupporting
confidence: 91%
“…Due to the nature of the food waste streams, previous studies might not attempt to make food waste-based diets isonitrogenous or isocaloric compared to the control diets 21 . Similar to this study, the protein and fat content in the food waste-based diet reported by Garnida et al 22 were also higher than the control diet.…”
Section: Introductionsupporting
confidence: 91%
“…Globally, about 1.3 billion tons of food waste is generated annually, with restaurant food waste (RFW) contributing to nearly 40% of total waste (FAO, 2011;Nasser et al, 2018). RFW is a putrescible organic waste that mainly consists of uneaten food and unusable leftovers (Chen et al, 2015;Garnida et al, 2022) and is associated with adverse health, socioeconomic, and environmental impacts due to its high moisture content and perishability (Ojha et al, 2020;Sobol et al, 2023). Nevertheless, RFW also contains valuable ingredients such as carbohydrates, protein, fats, vitamins, fiber, and minerals, making it a promising source of nutrients (Noori et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…GHG emissions from the decomposition of food waste are generally considered "emissions in vain", as they are a useful resource for recycling [29]. Instead, most of the wasted food ends up in landfills or dumping sites where it decomposes and generates leachate that percolates into the ground and contaminates our soil and groundwater [30,31]. Almost 22% of the total municipal solid waste is food waste [29].…”
Section: Introductionmentioning
confidence: 99%